Development of Integrated Comic Learning Media with Islamic Values - Usman, Yessy -; Purwanto, Hadi; Minarti, Agus; Robiah, Siti (Biosfer: Jurnal Tadris Biologi, 2024)
This research aims to determine the quality and feasibility of comics as a learning medium using research and development methods with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The research instruments included validation questionnaires measuring students' and teachers' interest in the developed product. The product was validated by three experts: a material expert with a score of 94%, a media expert with 83%, and a religious expert with 95%. All three validation results fall under the "very feasible" category. Based on the teacher assessment response, the product scored 88%, which is categorized as "very practical." Similarly, the student response scored 85%, which was also categorized as "very practical." These results indicate that the product is feasible and practical for teachers in learning. The advantages of the developed media include its portability for learning anywhere, the presentation of material with varied images, the inclusion of Qur'anic verses in each study section, and the integration of learning videos.ABSTRAK : Penelitian ini bertujuan mengetahui kualitas komik dan kelayakan komik sebagai media pembelajaran menggunakan metode penelitian dan pengembangan Research and Development (R&D) dengan model ADDIE (Analysis, Design, Development, Implementasion and Evaluation). Instrumen dalam penelitian ini adalah lembar angket validasi dan angket respon kemenarikan siswa dan guru terhadap produk. Produk ini divalidasi oleh tiga ahli yaitu ahli materi dengan perolehan persentase sebesar 94%, ahli media sebesar 83% dan ahli agama sebesat 95%. Ketiga hasil validasi tersebut masuk pada kriteria ’sangat layak’. Berdasarkan hasil respon penilaian guru adalah 88% yang juga termasuk dalam kategori ’sangat praktis’. Sedangkan hasil respon siswa menunjukkan nilai sebesar 85% dengan kriteria ’sangat praktis’. Berdasarkan hasil tersebut, dapat disimpulkan bahwa produk layak dan praktis sehingga dapat digunakan oleh guru untuk pembelajaran. Adapun keunggulan media yang dikembangkan yaitu komik bisa digunakan dimana saja untuk proses pembelajaran, materi yang disajikan dengan gambar bervariasi, adanya ayat-ayat Al-Qur’an disetiap kajian materi dan dilengkapi dengan video pembelajaran.